Eosinophilic Meningitis and Intracranial Haemorrhage: Can it be Neuro-Gnathostomiasis? - Basnet, Srijana; Shrestha, Laxman; Poudel, Daman Raj (Journal of Nepal Paediatric Society, 2019)
Peripheral eosinophilia is commonly encountered in our clinical practice. In this case report, we present a child who presented with hemorrhagic stroke and was finally diagnosed of eosinophilic meningitis. In this case report, we also propose probable etiologic agent.